In vitro antibacterial activity, biofilm formation inhibition and chromatographic profile of methanolic extracts of two Pterocaulon species against MRSA. Issue 24 (17th December 2022) - Burgos-Edwards, Alberto; Franco, Sergio; Salinas, Claudia; Florentín, Melissa; García, Lourdes; Guillén, Rosa; Alvarenga, Nelson
Abstract: The methanolic extracts of Pterocaulon alopecuroides and Pterocaulon angustifolium were assayed for antibacterial activity and biofilm formation inhibition of four community-acquired-MRSA isolates representative of ST30 t975, ST30 t021, ST5 t311, and ST4335 t008 clones that are responsible for invasive infections in Paraguayan children. Both Pterocaulon extracts showed significant antibacterial activity with a minimum inhibitory concentration of 200 µg/mL against the four isolates. P. angustifolium showed inhibition of biofilm formation for the four isolates, whereas P. alopecuroides showed inhibition for three of them. The chemical constituents were identified by liquid chromatography coupled to tandem mass spectrometry. Phenolic compounds were detected in the two species as well as coumarins. These results showed that these plants are sources of compounds with activity against MRSA. GRAPHICAL ABSTRACT: UF0001